2009
DOI: 10.1108/03684920910991469
|View full text |Cite
|
Sign up to set email alerts
|

Supplier evaluation model for computer auditing and decision‐making analysis

Abstract: PurposeThe purpose of this paper is to present a model and a supporting approach for effective supplier selection decisions.Design/methodology/approachStructural equation modeling (SEM) and confirmatory factor analysis are applied to test the evaluation principles and samples. Next, the data tested by SEM is used for artificial neural network (ANN) by Likert and fuzzy scales to structure a classification model, accompanying with canonical discriminate analysis (CANDISC) to diminish variables. After the trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It also reinforces the relative novelty of the research, being an indicator of information need that is still to be met by emerging provision of data. Control of information, not physical assets, is the key to success (Shih, et al, 2009). Success requires disseminating information that is to the firm"s advantage and protecting information that is the core of the firm"s business (Sullivan, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…It also reinforces the relative novelty of the research, being an indicator of information need that is still to be met by emerging provision of data. Control of information, not physical assets, is the key to success (Shih, et al, 2009). Success requires disseminating information that is to the firm"s advantage and protecting information that is the core of the firm"s business (Sullivan, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Research demonstrate that the fuzzy concepts are widely used in a supplier selection process (Montazer et al, 2009;Díaz-Madroñero et al, 2010;Dalalah et al, 2011;Yu et al, 2012;Dymova et al, 2013;Ghorbani et al, 2014;Liou et al, 2014;Mukherjee, 2016). Fuzzy linguistic terms are used to deal with linguistic group decision-making problems (Hatami-Marbini et al, 2013) that are not precisely known and they are reported in different supplier selection models (Yang et al, 2008;Shih et al, 2009;Amindoust et al, 2012;Ho et al, 2012;Zouggari and Benyoucef, 2012). However, applying the LOWA operator to deal with linguistic terms is still missing in SSTs.…”
Section: Rankmentioning
confidence: 99%
“…The authors proposed six main categories of criteria for selecting a supplier, including purchase costs, product quality, reliability, technical support, collaboration and financial performance. Shih et al (2009) submitted nine criteria for the supplier evaluation and selection based on four research papers. These criteria include price, product quality, distribution, technical support, cooperation and association, brand reputation, geographic location, financial position and available relationship.…”
Section: Research Backgroundmentioning
confidence: 99%